A New All-Solid-State Hyperbranched Star Polymer Electrolyte for Lithium Ion Batteries: Synthesis and Electrochemical Properties. (10th September 2016) - Wang, Ailian; Xu, Hao; Zhou, Qian; Liu, Xu; Li, Zhengyao; Gao, Rui; Wu, Na; Guo, Yuguo; Li, Huayi; Zhang, Liaoyun
Highlights: A new hyperbranched multi-arm star polymer was successfully synthesized. The star polymer electrolyte has good thermal stability and forming-film property. The ion conductivity electrolyte can reach 8.3 × 10 −5 S cm −1 at room temperature. The star polymer electrolyte has wide electrochemical windows of 4.7 V. Abstract: A new hyperbranched multi-arm star polymer with hyperbranched polystyrene (HBPS) as core and polymethyl methacrylate-block-poly(ethylene glycol) methyl ether methacrylate(PMMA- b -PPEGMA) as arms was firstly synthesized by atom transfer radical polymerization. The obtained hyperbranched multi-arm star polymer (HBPS-(PMMA- b -PPEGMA)x ) exhibited good thermal stability with a thermal decomposition temperature of 372 °C. The transparent, free-standing, flexible polymer electrolyte film of the blending of HBPS-(PMMA- b -PPEGMA)x and lithium bis(trifluoromethanesulfonyl) imide (LiTFSI) was successfully fabricated by a solution casting method. The ionic conductivity of the hyperbranched star polymer electrolyte with a molar ratio of [EO]/[Li] of 30 could reach 8.3 × 10 −5 S cm −1 at 30 °C (with the content of PPEGMA of 83.7%), and 2.0 × 10 −4 S cm −1 at 80 °C (with the content of PPEGMA of 51.6%). The effect of the concentration of lithium salts on ionic conductivity was also investigated. The obtained all-solid-state polymer electrolyte possessed a wide electrochemical stability window of 4.7 V ( vs. Li + /Li), and a lithium-ion transference number ( tLi + ) up to 0.31. The interfacial impedance of the fabricated Li│polymer electrolyte│Li symmetric cell based on hyperbranched star multi-arm polymer electrolyte exhibited good interfacial compatibility between all-solid-state polymer electrolyte and electrodes. The excellent properties of the hyperbranched star polymer electrolyte made it attractive as solid-state polymer electrolyte for lithium-ion batteries.